Hepatic Sarcoidosis: Current Concepts and Treatments - Rossi, Geoffrey; Ziol, Marianne; Roulot, Dominique; Valeyre, Dominique; Mahévas, Matthieu (Seminars in Respiratory and Critical Care Medicine, 2020)
Hepatic sarcoidosis is a relatively common manifestation of extrapulmonary sarcoidosis. It occurs in 20 to 30% of cases and is rarely severe. However, a cluster of patients may develop severe complications such as cirrhosis and portal hypertension. In this review, we describe the current knowledge of clinical, biological, pathological, and radiological features of liver involvement in sarcoidosis and discuss essential clues for management and treatment.
Keywords: sarcoidosis; hepatic sarcoidosis; liver; cholestasis; granulomas